Ischemic conditioning: the challenge of protecting the diabetic heart - Wider, Joseph; Przyklenk, Karin (Cardiovascular Diagnosis and Therapy, 2014)
The successful clinical translation of novel therapeutic strategies to attenuate lethal myocardial ischemia-reperfusion injury and limit infarct size has been identified as a major unmet need, and is of particular importance in patients with type-2 diabetes. There is a wealth of preclinical evidence that ischemic conditioning (encompassing the three paradigms of preconditioning, postconditioning and remote conditioning) is profoundly cardioprotective and, via up-regulation of endogenous signaling cascades, renders the heart resistant to infarction. However, current phase II trials aimed at exploiting ischemic conditioning for the clinical treatment of myocardial ischemia-reperfusion injury have yielded mixed results, possibly reflecting the emerging concern that the efficacy of conditioning-induced cardioprotection may be compromised in the diabetic heart. Our goal in this review is to provide a summary of our present understanding of the effect of type-2 diabetes on the infarct-sparing effect of ischemic conditioning, and the challenges of limiting ischemia-reperfusion injury in the diabetic heart.